The Relationship Between Exposure to Higher Levels of Morally Principled Thinking and the Development of Moral Decision Making Competencies of Student-Athletes - (:unkn) unknown (My University, 2011)
At intercollegiate athletics' most competitive level, NCAA Division I, student-athletes frequently experience national attention from media outlets, increased pressure to perform from coaches, celebrity status from society, and extreme demands of time that leave little room for student error or exploration. As media coverage of student-athlete crime expands, the question of how participation in intercollegiate athletics effects student-athlete development, specifically moral development, emerges. From student development theory, it is known that one way to influence the growth of moral development is to expose students to higher levels of morally principled thinking. The purpose of this study was to examine the relationship between the exposure to higher levels of morally principled thinking and the development of moral decision making competencies. Through quantitative methodology, participants (n = 178) completed two study instruments: a self-made questionnaire measured the possible exposure to higher levels of morally principled thinking and Georg Lind's Moral Judgment Test, which measured the participants' abilities to make moral decisions. Multiple regression analyses revealed that the family's involvement in the pre-collegiate years is most influential on the development of moral decision making competencies. During collegiate years, coaches are most influential in the lives of student-athletes.
Keywords: College athletes--Psychology; Moral development